The impact of solute carrier proteins on disrupting substance regulation in metabolic disorders: insights and clinical applications - Du, Jiangxia; Shen, Minhui; Chen, Jiajia; Yan, Hao; Xu, Zhifei; Yang, Xiaochun; Yang, Bo; Luo, Peihua; Ding, Kefeng; Hu, Yuhuai; He, Qiaojun (Frontiers in Pharmacology, 2025)
Carbohydrates, lipids, bile acids, various inorganic salt ions and organic acids are the main nutrients or indispensable components of the human body. Dysregulation in the processes of absorption, transport, metabolism, and excretion of these metabolites can lead to the onset of severe metabolic disorders, such as type 2 diabetes, non-alcoholic fatty liver disease, gout and hyperbilirubinemia. As the second largest membrane receptor supergroup, several major families in the solute carrier (SLC) supergroup have been found to play key roles in the transport of substances such as carbohydrates, lipids, urate, bile acids, monocarboxylates and zinc ions. Based on common metabolic dysregulation and related metabolic substances, we explored the relationship between several major families of SLC supergroup and metabolic diseases, providing examples of drugs targeting SLC proteins that have been approved or are currently in clinical/preclinical research as well as SLC-related diagnostic techniques that are in clinical use or under investigation. By highlighting these connections, we aim to provide insights that may contribute to the development of improved treatment strategies and targeted therapies for metabolic disorders.